Relationship between the red cell distribution width-to-platelet ratio and in-hospital mortality among critically ill patients with acute myocardial infarction: a retrospective analysis of the MIMIC-IV database - Quan Zhou; Li Tong; Yan-Qiong Liu; Jin Hua Shen; Min B O; Xiang-Jie Duan; Ya Fen Guo; Xue Qing Zhang (BMJ Open, 2022)
Objectives We aimed to investigate the association between red cell distribution width-to-platelet ratio (RPR), and in-hospital mortality in critically ill patients with acute myocardial infarction (AMI).Design A retrospective cohort study.Setting Data were collected from the Medical Information Mart for Intensive Care database (MIMIC-IV) consisting of critically ill participants between 2008 and 2019 at the Beth Israel Deaconess Medical Centre in Boston.Participants A total of 5067 patients with AMI were enrolled from the MIMIC-IV database.Primary and secondary outcome In-hospital mortality.Results A total of 4034 patients survived, while 1033 died. In a multiple regression analysis adjusted for age, weight and ethnicity, RPR also showed a positive correlation with in-hospital mortality (HR 1.91, 95% CI 1.42 to 2.56, p<0.0001). Moreover, after adjusting for additional confounding factors, obvious changes were observed (HR 1.63, 95% CI 1.03 to 2.57, p=0.0357). In model 2, the high ratio quartile remained positively associated with hospital mortality compared with the low ratio quartile (HR 1.20, 95% CI 1.01 to 1. 43), with a p-value trend of 0.0177. Subgroup analyses showed no significant effect modifications on the association between RPR and in-hospital mortality in the different AMI groups (p>0.05).Conclusion RPR is an independent predictor of in-hospital mortality in critically ill patients with AMI.